Psychological distress among women undergoing in vitro fertilization-embryo transfer: A cross-sectional and longitudinal network analysis - Wu, Liuliu; Sun, Lijing; Wang, Juan; Sun, Yaoyao; Zhang, Xuan; Huang, Yongqi; Lu, Yan’e; Cao, Fenglin (Frontiers in Psychology, 2023)
Background Women undergoing in vitro fertilization-embryo transfer (IVF-ET) treatment were generally found to experience varying degrees of psychological distress across the treatment. Existing studies focused on total scores and diagnostic thresholds to characterize the symptoms’ severity, which might hinder scientific progress in understanding and treating psychological distress. Aims We aimed to investigate (a) how depression and anxiety symptoms are interconnected within a network, and (b) the changes of the network (symptom connections and network centralities) over time, in women undergoing in vitro fertilization-embryo transfer. Methods A 4-wave longitudinal study was designed with 343 eligible women recruited from the Reproductive Medicine Center of a tertiary hospital in China. The network models were created to explore the relationship and changes between psychopathology symptoms both within and across anxiety and depression, with anxiety measured by the Generalized Anxiety Disorder-7 and depression measured by the Patient Health Questionnaire-9. Symptom network analysis was conducted to evaluate network and network properties, network centrality, and bridge centrality, as well as change trajectory network. Results For the strength centrality, “inability to control worry” and “worrying too much” were the most central symptoms at T1; however, these symptoms decreased. The centrality of “sadness” and “guilt” tended to increase steadily and became dominant symptoms. For bridge centrality indices, several bridge symptoms were identified separately from T1 to T4: “irritability,” “concentration difficulties,” “nervousness,” and “restlessness”; “guilt” exhibited increased bridge symptoms. Furthermore, the change trajectory network indicated that “suicide ideation” became more closely related to guilt but not to worrying too much over time. Conclusion This study provides novel insights into the changes in central features, connections, and bridge symptoms during IVF-ET treatment and identified several bridge symptoms separately at different stages, which could activate the connection between psychopathology symptoms. The results revealed that sense of guilt was associated with worsening psychopathology symptoms, indicating that future psychological interventions should target guilt-related symptoms as a priority.